Elastic waves for miniaturized piezoelectric sensors: applications to physical quantity measurements and chemical direction - HAUDEN, D. (Archives of Acoustics, 1991)
The frequency is the quantity measured with the best accuracy and time and length standards are defined with it. In the domain of the metrology closer of manufacturing applications (process control or instrumentation), sensors based on the frequency variation of oscillators, are potentially interesting because several reasons: high resolution, good sensitivity and digital signal by accounting. This paper is dedicaced to an overview of oscillators used as sensor in which general principles and definitions are presented and illustrated with different devices built in SAW technologies (temperature, pressure, acceleration).Different technological ways can be used to build the sensitive SAW sensor and chemical detector applications enable to describe the different possibilities as quartz or LiNbO3 substrates or silicon substrate using Rayleigh waves or Lamb modes.